Empty Hat: - Marc W. Herold (Revista Espaço Acadêmico, 2021)
No major foreign equity investment in either the goods or the resources-producing sectors in Afghanistan has been made, notwithstanding Karzai's frantic travels abroad seeking to woo investors. This contrasts sharply with Afghanistan under the Taliban [1996-2001] when both the giant U.S. oil firm, UNOCAL, committed to building a trans-country gas pipeline and a private New Jersey-based enterprise, Telephone Systems International Inc., secured a license from the Taliban to set up an integrated, high-tech communications network costing $240 mn.  The Taliban for all their faults, were able to put in place a degree of  political stability and the means to enforce contracts - after all, in one year they reduced poppy cultivation to next to nothing. Under the "non failed state" of Karzai, on the other hand, poppy production has soared. Afghanistan's share of the world heroin market rose from 12% in 2001, to 76% by 2003.